2015
DOI: 10.1080/20477724.2015.1126033
|View full text |Cite
|
Sign up to set email alerts
|

Elevated prevalence of malnutrition and malaria among school-aged children and adolescents in war-ravaged South Sudan

Abstract: Emerging as a sovereign state from decades of civil war, the Republic of South Sudan now faces poverty, a lack of health care infrastructure, a high burden of infectious diseases and a widespread food insecurity. School-aged children and youth, in particular, represent a high-risk demographic for malnutrition and infectious diseases. We screened 109 school-aged children and youth for nutritional status and malaria antigenaemia in Akuak Rak, South Sudan, and found a large proportion of underweight (77/109 = 73%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
(32 reference statements)
0
8
1
1
Order By: Relevance
“…[42] who asserted that stunted children are more likely to have malaria infection and illness than non-stunted. However, it contradicts the finding of Charchuk et al [16] in southern Sudan where no association was observed between malnutrition and malaria. Filol et al [43] in Senegal also observed no association between stunting and underweight forms of malnutrition and malaria attacks while at the same time observing lower risk of attacks among wasted children.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…[42] who asserted that stunted children are more likely to have malaria infection and illness than non-stunted. However, it contradicts the finding of Charchuk et al [16] in southern Sudan where no association was observed between malnutrition and malaria. Filol et al [43] in Senegal also observed no association between stunting and underweight forms of malnutrition and malaria attacks while at the same time observing lower risk of attacks among wasted children.…”
Section: Discussioncontrasting
confidence: 92%
“…During a seasonal transmission in a rural area of the Gambia, a cohort study of children under five showed that malnutrition was not associated with an increased risk of malaria [15]. In the same vein, Charchuk et al [16] in Southern Sudan found no association between malnutrition and malaria. However, The World Health Organization's Comparative Risk Assessment Project affirm that children with moderate and severe under-weight had an increased, though not statistically significant risk of malaria attack compared with those who had improved nutritional status [17].…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, social determinants of health in countries in conflict tend to differ as morbidity and mortality are associated with conflict (World Health Organization 2008 ). More importantly, wars and civil unrest are closely associated with child malnutrition, which in turn is associated with increased risk of obesity, hypertension, cardiovascular disease, and type 2 diabetes (Devakumar et al 2014 ; Charchuk et al 2015 ). This leads to the intergenerational effects of war on obesity and the doubled burden of undernutrition in countries affected by wars or experiencing chronic civil unrest (Devakumar et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, an observational follow-up study in a rural area of Senegal indicated that wasted children were at lower risk of experiencing at least one subsequent clinical malaria attack while other studies conducted in Western Ethiopia, Kenya, Gambia and Uganda showed that there was no relationship between baseline nutritional status and subsequent incidence of malaria among the children studied [13,14,15,16,17]. A previous study in South Sudan among school children showed that nutritional status was not associated with the occurrence of malaria [18].…”
Section: Introductionmentioning
confidence: 89%